Current Prospects: Drug acting against resistant Tuberculosis - ., Monika; Yadav, Rakesh (International Journal of Membrane Science and Technology, 2023)
The most lethal disease tuberculosis is caused by Mycobacterium tuberculosis and the risk has worsened with the appearance of drug resistance, in particular multi drug resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB). Antimicrobial resistance (AMR), is one of the most dominant health hazard that has emerged in the 21st century. This review embrace the drug resistance in MTB and inclusive overview of present phenotypic and molecular approaches for drug vulnerability testing, with particular attention to the methods endorsed and recommended by the WHO. “Drug resistance is an unavoidable consequence of the use of drugs; however, the appearance of multi-drug resistance can be managed by accurate diagnosis and perfect regimens. Moreover, the discovery of new chemical entities targeting specific vulnerabilities in the M. tuberculosis bacterium has gained significant attention. Various drug candidates are in different stages of preclinical and clinical development. Additionally, combination therapy approaches involving multiple drugs with complementary mechanisms of action are being explored to overcome drug resistance and improve treatment outcomes In recent years, funded collaborative efforts of researchers from academia, not-for-profit virtual R&D organizations and industry have resulted in the continuous growth of the TB drug discovery and development pipeline. While substantial progress has been made in the field of drug development against resistant TB, several clinical trials. Nonetheless, the current prospects in drug development against resistant tuberculosis hold great promise for improving treatment outcomes, reducing transmission, and ultimately eradicating this devastating disease.